Industrial Spaces That Won’t Go Away - Tomczok, Paweł (Porównania, 2023)
The article takes up the issue of space in the economics and philosophy of capitalism. Based on excerpts from Marx’s writings, I reconstruct the idea of annihilation of space and the metabolic rift. Using James Moor’s contemporary interpretations of these concepts, the article discusses industrial spaces in the Capitalocene. The perspective of the oikos, combining economics and ecology, has allowed me a new perspective on the issues of industrialization and deindustrialization and a reading of different cultural texts that deal with the issue of human impact on the environment. The second part of the article describes examples of degradation of the landscape of the Upper Silesian Coal Basin, portrayed in selected films and photographs. The conclusion asks about the possibility of a hermeneutics of industrial space: the possibility of life after the disaster and the creation of meaning in a tentacular entanglement with beings other than humans.